Enhanced hydrogen adsorption properties of mesoporous nano-TiO2@SnO2. (15th February 2023) - Rajendran, Saravanan; Gnanasekaran, Lalitha; Hoang, Tuan K.A.; Diaz-Droguett, D.E.; Gracia, F.; Gracia-Pinilla, M.A.
Highlights: Hydrogen measurements of mesoporous TiO2 @SnO2 composite were accomplished by quartz crystal (QC) microbalance method. The Titania oxidation states play a predominant role in the procurement of larger H2 adsorption. The synergistic effect of the composite system offers more Ti 3+ active sites. The Ti 4+ and Sn 4+ reveal fragile Kubas binding mechanism that facilitated the hydrogen adsorption. Abstract: Today, hydrogen as being one of the most advantageous energy supplies for various applications and specifically not with carbon emissions, alluring strategies are made possible for its production and storage. Since the metal oxides (MOs) semiconductors give rise to the development of new technologies related to renewable energy and environmental issues, this work is envisioned to study the hydrogen adsorption properties of TiO2 @SnO2 catalyst synthesized via novel approach by integrating sol–gel and thermal decomposition methods. The synthesized TiO2 and its composite have been analyzed by sophisticated instruments to reveal the drastic enhancement of hydrogen adsorption. In this work, hydrogen measurements were accomplished by quartz crystal (QC) microbalance method. The Raman scattering experiment of the composite revealed the lower peak intensity compared with pure TiO2, which demonstrated the surface defects that created oxygen vacancies with reduced oxidation states of the metal centers. Meanwhile, the mesoporous nanostructure of TiO2 @SnO2 could be confirmed via High resolution transmission electron (HR-TEM) microscopic analysis. Besides, the intermediate states of the composite were analyzed through Photoluminescence (PL) spectra which demonstrated the delay in recombining charges. The Barrett-Joyner- Halenda (BJH) method illustrated the larger pore size and pore volume with decreased surface area of the composite. The addition of SnO2 into TiO2 has reported 4 times greater the adsorption of pristine TiO2 particles, because of the capacity of SnO2 to hinder pores. Moreover, the titania oxidation states play a predominant role in the procurement of larger H2 adsorption. Also, the Ti 4+ and Sn 4+ reveal fragile Kubas type of adsorption that facilitated the hydrogen storage.